1981
DOI: 10.1172/jci110228
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroids block binding of chemotactic peptide to its receptor on granulocytes and cause disaggregation of granulocyte aggregates in vitro.

Abstract: A B S T R A C T Inhibition of complement-mediated granulocyte aggregation has recently been proposed as a mechanism of action of high-dose corticosteroids in shock states. Postulating that such inhibition might be effected through alteration of receptor function, we examined the effect of methylprednisolone (MP), hydrocortisone (HC), and dexamethasone (DEX) on the extent and kinetics of binding of the synthetic chemotaxin f-methionine-leucine-phenylalanine (FMLP) to its specific receptor on the granulocyte s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0
3

Year Published

1983
1983
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(15 citation statements)
references
References 32 publications
2
10
0
3
Order By: Relevance
“…The agreement of percent aggregation by microscopy with STKR or STKS demonstrated that the number of aggregates counted along with the unaggregated cells was negligible. Our results confirmed the inhibitory role of corticosteroids, at high dosage, on PMN aggregation (Skubitz et al 1981). To explain this, an effect that excludes the FAS action on aggregation should be invoked.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The agreement of percent aggregation by microscopy with STKR or STKS demonstrated that the number of aggregates counted along with the unaggregated cells was negligible. Our results confirmed the inhibitory role of corticosteroids, at high dosage, on PMN aggregation (Skubitz et al 1981). To explain this, an effect that excludes the FAS action on aggregation should be invoked.…”
Section: Discussionsupporting
confidence: 88%
“…Aggregation induced by the former group of stimuli measures the intrinsic aggregation capacity of neutrophils (Wallis et al 1986), whereas PMN aggregation by plasma or serum, both unactivated and activated, also reflects humoral effects on the aggregation (Craddock et al 1977c;Hashimoto & Hurd 1981;Camussi et al 1981;Abramson et al 1983;Ringertz et al 1985;Berliner et al 1987). On the contrary, high-dose corticosteroids inhibit PMN aggregation in vivo and in vitro (Schumer 1976;Hammerschmidt et al 1979;Skubitz et al 1981).…”
mentioning
confidence: 99%
“…The negative correlation of granulocyte adherence and PMN number (figure 2) that we observed is similar to the neutrophilia and hypoadherence that occurs after chemotactic factors are experimentally infused in vivo (5,21,30,(34)(35)(36)(37)(38), and tends to support this hypothesis (39). The granulocyte hyporesponsiveness might also be explained by the presence of significant numbers of immature granulocytes with different functional characteristics (21).…”
Section: Discussionsupporting
confidence: 79%
“…Thus, the prevention by dexamethasone of the fall in blood pressure in response to LPS is not related to inhibition of the formation cyclooxygenase metabolites. Whether other well documented actions of glucocorticosteroids, such as inhibition of the release of endorphins (Simatov, 1979) or platelet-activating factor (Braquet et al, 1987), and/or inhibition of neutrophil activation (Goldstein et al, 1976;Hammerschmidt et al, 1979;Schubitz et al, 1981) contribute to the observed haemodynamic effects of dexamethasone in endotoxic shock warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%